The Influence Of Sales Growth, Price To Book Value (Pbv), Earning Per Share (Eps), And Dept Equity Ratio (Der) On Stock Price Value on Empirical Study of Banking Companies Listed on the IDX in 2019 – 2022 - Rama Einar Maska Praditya*; Kurnia Rina (Universitas Syiah Kuala, 2023)
This research aims to analyze the influence of sales growth ratio, price to book value, earnings per share, dept equity ratio on stock prices. The population of this research is banking companies listed on the Indonesia Stock Exchange (BEI) in 2019-2022. The research sample was obtained using purposive sampling, where there were 28 manufacturing companies that met all the criteria, resulting in 112 data which were then outliers to become 108 data as the research sample. The data source in this research was obtained from the BEI website. Type of quantitative research. The analytical tool used is SPSS version 25 with multiple linear regression testing. The results of the research analysis show that price to book value (PBV) and earnings per share (EPS) have a significant effect on the value of share prices.